Quandaries
and Queries |
|||

Out of interest could you please answer the following questions? U'(X) - U(X) = 0; U(0) = 2 and U''(X) - U'(X) = 0; U'(0) = U(0) = 2 Kind Regards David |
|||

Hi David, If U'(X) - U(X) = 0 then U'(X) = U(X) and you can either recognize immediately that
or you can proceed as follows
The initial condition is that U(0) = 2 so U(0) = A e For the second problem let V(X) = U'(X) and you have
This is exactly the first problem. Hence you know V(X) so you can solve
To find U(X). Harley |